Should We Delay Urodynamic Study When Patients With Spinal Cord Injury Have Asymptomatic Pyuria? - EunYoung Kim; Hye Jin Lee; Onyoo Kim; In Suk Park; Bum-Suk Lee (Annals of Rehabilitation Medicine, 2021)
Objective To assess the incidence of urinary tract infection (UTI) with post-urodynamic study (post-UDS) in patients with spinal cord injury (SCI) and study its relationship with pre-UDS pyuria. Methods Patients with SCI who were hospitalized and underwent UDS during a 4-year period were reviewed. Patients with pre-test lower urinary tract symptoms were excluded. Urinalysis and urine culture were performed before and 24 hours after UDS. Prophylactic antibiotics were administered for 5 days starting from the morning of the UDS. UTI was defined as bacteriuria with accompanying symptoms. Results Of 399 patients reviewed, 209 (52.4%) had pyuria in pre-UDS urinalysis, and 257 (64.4%) had bacteriuria in pre-UDS culture. Post-UDS UTI occurred in 6 (1.5%) individuals who all complained of fever: 5 (2.4%) of the post-UDS UTI cases occurred in patients with pre-UDS pyuria, and 1 (0.5%) in a person without. The differences between groups were not statistically significant (p=0.218). Of 221 patients with bacteriuria (gram-negative isolates) on pre-UDS culture, resistance to ciprofloxacin, cephalosporin, and trimethoprim/sulfamethoxazole (TMP/SMT) was noted in 52.9% (117 cases), 57.0% (126 cases), and 38.9% (86 cases), respectively. Conclusion No difference was found in the prevalence of post-UDS UTI based on the presence of pyuria in pre-UDS urinalysis. UDS may be performed even in SCI cases of pre-UDS pyuria without increasing the prevalence of post-UDS UTI if prophylactic antibiotics are administered. TMP/SMT could be used as a first-line antibiotic for the prevention of post-UDS UTI in Korea.